2018
DOI: 10.3389/fict.2018.00003
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of Helping Introductory Physics Students Transfer Their Learning by Engaging with a Self-Paced Learning Tutorial

Abstract: With advances in digital technology, research-validated self-paced learning tools can play an increasingly important role in helping students with diverse backgrounds become good problem solvers and independent learners. Thus, it is important to ensure that all students engage with self-paced learning tools effectively in order to learn the content deeply, develop good problem-solving skills, and transfer their learning from one context to another. Here, we first provide an overview of a holistic framework for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
3
0
1
Order By: Relevance
“…Por otra parte, el análisis de datos acerca del ritmo de aprendizaje permite llevar información objetiva de los estudiantes hallando los elementos que deben mejorarse para ofrecer contenidos y rutas de aprendizaje personalizadas (Aguilar, 2018;Aslan et al, 2020;Gorbunovs et al, 2018;Maseleno et al, 2018). Cuando el estudiante lleva su propio ritmo de aprendizaje desarrolla habilidades, permitiéndole resolver problemas y transferir el conocimiento a diferentes contextos (Marshman et al, 2018). La principal debilidad en este modelo educativo es la escasa cantidad de estudiantes presentes en el aula, siendo necesario el apoyo de la tecnología que posibilita el acceso al 20.…”
Section: Categoría Aprendizaje Personalizado Subcategoría Ritmos De A...unclassified
“…Por otra parte, el análisis de datos acerca del ritmo de aprendizaje permite llevar información objetiva de los estudiantes hallando los elementos que deben mejorarse para ofrecer contenidos y rutas de aprendizaje personalizadas (Aguilar, 2018;Aslan et al, 2020;Gorbunovs et al, 2018;Maseleno et al, 2018). Cuando el estudiante lleva su propio ritmo de aprendizaje desarrolla habilidades, permitiéndole resolver problemas y transferir el conocimiento a diferentes contextos (Marshman et al, 2018). La principal debilidad en este modelo educativo es la escasa cantidad de estudiantes presentes en el aula, siendo necesario el apoyo de la tecnología que posibilita el acceso al 20.…”
Section: Categoría Aprendizaje Personalizado Subcategoría Ritmos De A...unclassified
“…This is especially useful for learning physics problem-solving, and students are required to describe the various aspects of the problems they solve later by using strategies learned at the beginning of the unit in the initial stage of problem-solving. Others have developed interactive problem-solving tutorials inspired by the cognitive apprenticeship framework [45,[128][129][130][131].…”
Section: A Cognitive Apprenticeship Modelmentioning
confidence: 99%
“…It's not just the time students spend on a particular task that matters for learning from problem-solving, but what is critical is that they are mentally engaged. For example, prior research [45,129,130] found that when students studied on their own from guided problem-solving tutorials with context-rich problems (which guided students to make decisions in a fashion somewhat similar to the computer coaches), many students simply glossed over them instead of thinking through each sub-problem and thus derived little benefit from them. But when students worked through the problem-solving tutorials in the presence of a researcher who only instructed students to think aloud while solving the problems and ensured that students were using the tutorial properly and thinking through the hints and guidance as directed, they did exceedingly well on subsequent transfer problems, with performance nearing the ceiling.…”
Section: Research-based Approaches To Foster Effective Problem-solvingmentioning
confidence: 99%
“…Multiple-choice questions may also be used as part of self-paced learning tools, e.g., self-paced learning tutorials, to give instant feedback to students based upon difficulties, and the results could also be followed up via in-class or online instruction that takes into account the students' difficulties found through their responses to the questions [65][66][67][68][69][70][71][72]. When students engage with such an approach to self-paced tutorials, student understanding is enhanced [73][74][75]. Similarly, welldesigned multiple-choice questions that incorporate common student difficulties can help facilitate a "Just-in-Time-Teaching" (JiTT) approach wherein pre-lecture feedback is gathered just before instruction takes place and serves to guide the instructor in addressing student difficulties.…”
Section: Multiple-choice Problems As a Formative Assessment Toolmentioning
confidence: 99%